2024
DOI: 10.1002/advs.202308040
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Active Carbon for Oxygen Reduction Reaction in Energy Conversion: Recent Advances and Future Perspectives

Shuling Liu,
Ao Wang,
Yanyan Liu
et al.

Abstract: The shortage and unevenness of fossil energy sources are affecting the development and progress of human civilization. The technology of efficiently converting material resources into energy for utilization and storage is attracting the attention of researchers. Environmentally friendly biomass materials are a treasure to drive the development of new‐generation energy sources. Electrochemical theory is used to efficiently convert the chemical energy of chemical substances into electrical energy. In recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 566 publications
0
0
0
Order By: Relevance
“…The pressing need for clean and sustainable energy due to global energy shortages and environmental pollution is driving a rapid shift to a towards electricity as the primary power source. , Therefore, sustainable development based on photo/electrochemical energy conversion and storage technologies is essential to expedite the transition to a clean and sustainable global energy system. It encompasses a wide range of technologies, primarily including energy conversion systems involving water decomposition to produce hydrogen and oxygen, nitrogen to ammonia, carbon dioxide to create value-added chemicals, and energy storage devices based on supercapacitors, metal-ion batteries, metal-air batteries, etc. Extensive studies have shown that various catalysts or electrode materials are key in driving the efficient and rapid development of these technologies. In this regard, noble metals of the platinum group (Pt, Ru, Ir, Pb, etc.) and their related compounds (IrO 2 , RuO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The pressing need for clean and sustainable energy due to global energy shortages and environmental pollution is driving a rapid shift to a towards electricity as the primary power source. , Therefore, sustainable development based on photo/electrochemical energy conversion and storage technologies is essential to expedite the transition to a clean and sustainable global energy system. It encompasses a wide range of technologies, primarily including energy conversion systems involving water decomposition to produce hydrogen and oxygen, nitrogen to ammonia, carbon dioxide to create value-added chemicals, and energy storage devices based on supercapacitors, metal-ion batteries, metal-air batteries, etc. Extensive studies have shown that various catalysts or electrode materials are key in driving the efficient and rapid development of these technologies. In this regard, noble metals of the platinum group (Pt, Ru, Ir, Pb, etc.) and their related compounds (IrO 2 , RuO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of ROS is complicated, involving multiple steps and intermediates during the ECL process. Specifically, ROS can be obtained by oxygen reduction reaction (ORR) under negative potential and oxygen evolution reaction (OER) under positive potential, which involves the generation of intermediates like O 2 •– , HO • , and H 2 O 2 and their mutual conversions. , Moreover, the generation of ROS can be affected by various factors, such as different potential ranges and scan directions. ,, More specifically, the dissolved O 2 is first reduced into O 2 •– , then converted into HO 2 – and further reduced into HO • under the different negative potentials in alkaline solution. , Meanwhile, HO • , HO 2 – , and O 2 •– can be directly formed under the different positive potentials by oxidation of HO – in alkaline solution. , These produced ROS at different potentials can affect the ECL performances of luminol-dissolved O 2 significantly. However, how these ROS influence the potential-resolved ECL pathways was unclear.…”
Section: Introductionmentioning
confidence: 99%